2007
DOI: 10.1103/physrevlett.98.226102
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Formation during the Oxidation of CO onPt{100}: A Mesoscopic Model

Abstract: Constantly changing irregular patterns of carbon monoxide (CO) and oxygen are seen during CO oxidation on platinum crystals in the [100] orientation. Ours is the first reaction-diffusion model to reproduce this pattern formation on physically feasible length and time scales, faithfully incorporating the available experimental data. Numerical simulations show patterns made up of CO and oxygen fronts moving at similar speeds to those seen in experiments [4][5][6].PACS numbers: 68.43. Bc,68.47.De,82.40.Ck Spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A number of theoretical approaches have been used to study the structure of the 12 C nucleus. State-of-the-art ab initio approaches such as Antisymmetrized Molecular Dynamics (AMD) [10,11], Fermionic Molecular Dynamics (FMD) [12], and a calculation on the QCD lattice, utilising Chiral Effective Field Theory [13], have all demonstrated the emergence of α-clustering from the nucleon-nucleon interaction. There have also been a number of attempts over the years to understand the structure directly in terms of possible α-particle building blocks.…”
Section: Alpha Cluster Models and The Thsr Wave Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of theoretical approaches have been used to study the structure of the 12 C nucleus. State-of-the-art ab initio approaches such as Antisymmetrized Molecular Dynamics (AMD) [10,11], Fermionic Molecular Dynamics (FMD) [12], and a calculation on the QCD lattice, utilising Chiral Effective Field Theory [13], have all demonstrated the emergence of α-clustering from the nucleon-nucleon interaction. There have also been a number of attempts over the years to understand the structure directly in terms of possible α-particle building blocks.…”
Section: Alpha Cluster Models and The Thsr Wave Functionmentioning
confidence: 99%
“…The alpha cluster model of Brink was refined in 2001 by Tohsaki, Horiuchi, Schuck and Röpke (THSR) [9]. They concluded that for states in 12 C with large radii, corresponding to large average α-α separations, the α-particles may retain their bosonic identities and produce the equivalent of a Bose-Einstein condensate. There is clear evidence indicating that the Hoyle state has an unusually large radius.…”
Section: Alpha Cluster Models and The Thsr Wave Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic oxidation of carbon monoxide (CO) by oxygen to carbon dioxide (CO 2 ) has been extensively studied in relation to air pollution control [190], which are catalyzed by both supported metal nanoparticles [191][192][193] and metal single-crystal surfaces [194][195][196][197][198][199][200][201][202][203][204][205]. It has been demonstrated that highly dispersed Ir/TiO 2 catalysts exhibit extremely high catalytic activity for CO oxidation below room temperature [206].…”
Section: Oxidation Of Co By Oxygenmentioning
confidence: 99%
“…In a recent letter, 15 we summarized numerical simulation results from the first faithful reaction-diffusion model to describe pattern formation in this system on experimentally realistic length and time scales. In this article, we focus on the derivation of the reaction-diffusion equations that define our model and present the results of numerical integrations and comparison with experiments in detail.…”
Section: Introductionmentioning
confidence: 99%